Thermodynamic Study on Molecular Interactions in Ternary Liquid Mixture of Morpholine, Cyclohexanone and Isoamyl Alcohol at 308.15 and 318.15 K - Rose Venis, A.; Rosario Rajkumar, X. (Asian Journal of Chemistry, 2011)
Densities, viscosities and ultrasonic velocities has been measured for the ternary mixture involving morpholine(1) + cyclohexanone(2) + isoamyl alcohol(3) at 308.15 and 318.15 K over the entire range of mole fraction. Thermodynamic parameters like excess volume, adiabatic compressibility, free volume, linear free energy, acoustic impedance, relative association and isentropic compressibility have been calculated. From these values the excess values are also calculated. The deviations of the liquid mixture from ideality have been explained based on the molecular interaction between unlike molecules.